TRAVELER’S KNOWLEDGE AND ATTITUDES TO ACCESS TOURISM HEALTH CENTRE AT GUNUNGKIDUL: CASE STUDY AT INDRAYANTI BEACH - Noval Ali Lating; Liena Sofiana (Epidemiology and Society Health Review (ESHR), 2020)
Background: Indrayanti beach located at Gunungkidul district, Yogyakarta. The number of tourists visited this beach has increased each year, meaning that it increases the health risks for the tourist and people involved, such as infectious diseases, blisters, lost, injured by objects or marine animals, sea water irritation. However, according to the previous study, a traveler who is accessing the Tourism Health Centre is low. This research aimed to identify the relationship between knowledge and attitude of the travelers in Indrayanti Beach to the traveler’s access to the Tourism Health Centre.Method: Quantitative analytical approach with a cross-sectional study design was applied in this study. Of 106 travelers was participate in this study that was recruited through accidental sampling. A tested questionnaire contained knowledge, and attitude was asked to the Indrayanti visitor. A Chi-square test was used to analyze the result.Results: There is a significant association between knowledge level (p=0.027) and attitude (p = 0.000) to the willingness to access the Tourism Health Centre. Conclusion: Knowledge and attitude are the primary aspects of the willingness to access the Tourism Health Centre.